Application of BIM and 3D Laser Scanning for Quantity Management in Construction Projects - Thu Anh Nguyen; Phong Thanh Nguyen; Sy Tien Do (Advances in Civil Engineering)
The construction industry has played an essential role in the process of modernization and industrialization and it has also been a major factor in determining the development of the infrastructure for other economic sectors. Construction companies consider the measurement of work progress, which often wastes time and has a low resolution, to be one of the most challenging problems faced by project management. Therefore, this research aimed to propose practical solutions by applying recent technological achievements of the 4.0 industrial revolution to improve the efficiency of the quantity management process. By utilizing the advantages and features of a BIM model and 3D laser scanning, this paper proposes that adopting a BIM model and 3D laser scanning has the potential to improve the accuracy and efficiency of the quantity management process. The case study demonstrated some typical tasks to evaluate accuracy and efficiency as well as to showcase the research proposal.